A case of multiple squamous papillomas in the trachea treated by rigid bronchoscopy. Issue 5 (1st April 2021) - Torii, Atsushi; Nishimura, Rieko; Oki, Masahide
Key message: Tracheal papilloma is a rare benign lung tumour. It often recurs and sometimes transforms into a malignant tumour. While historically radical resection has been the primary treatment, endobronchial resection, a less invasive procedure to manage the airway using a flexible and rigid bronchoscope, was effectively used in our patient. Abstract : Tracheal papilloma is a rare benign lung tumour that often recurs and can become malignant. The primary treatment is often radical resection; however, we effectively used endobronchial resection, a less invasive procedure to manage the airway using a flexible and rigid bronchoscope, in our patient.